2020
DOI: 10.1103/physrevb.102.024301
|View full text |Cite
|
Sign up to set email alerts
|

Two-path phonon interference resonance induces a stop band in a silicon crystal matrix with a multilayer array of embedded nanoparticles

Abstract: In this work, we report a new stop-band formation mechanism by performing the atomistic Green's function calculation and the wave-packet molecular dynamics simulation for a system with germanium-nanoparticle array embedded in a crystalline silicon matrix. When only a single nanoparticle is embedded, the local resonance, induced through destructive interference between two different phonon wave paths, gives rise to several sharp and significant transmittance dips. On the other hand, when the number of embedded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This effect is caused mainly by the single-path Bragg-like phonon interference. 45 When the periodic length of the SL decreases, the phonon transmission of low-frequency phonons recovers to a level comparable to that of the HJ, which leads to an increased ITC.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is caused mainly by the single-path Bragg-like phonon interference. 45 When the periodic length of the SL decreases, the phonon transmission of low-frequency phonons recovers to a level comparable to that of the HJ, which leads to an increased ITC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the superlattice structure, Hu et al [94] proposed an approach based on two-path phonon interference to achieve a stop band and the total reflection of the phonons in a multilayer array with a crystalline silicon matrix and embedded germanium nanoparticles. As shown in Figure 3(b), the phonon transmission decreases dramatically as the number of nanoparticle layers increases.…”
Section: Phonon Interference Effectsmentioning
confidence: 99%
“…To this aim, a lot of researchers have suggested unique nanostructures tailoring phonon transport in light of experiments and theories. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] A coherent phonon effect was observed at room temperature in the superlattices (SLs) with several nm periodicity. 10,18 In the twodimensional Si phononic crystals with a nanohole periodicity of ∼500 nm, the ballistic phonon particle-like transport was detected.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] In such materials, recent theoretical studies reported the interesting phonon wave properties indicating that a nanodot (ND) can work as a resonator in analogy with photonic crystals. 16,19 However, the actual nanostructures include unwanted and undefined structural features, such as interface defects, impurities, strain, etc., making it difficult to classify the contribution of each scattering process to phonon transport and especially to observe an interesting phonon wave effect.…”
Section: Introductionmentioning
confidence: 99%